(untitled) (ENTHYMEMA, 2020)
The artist-character is a recurrent figure in Italian fiction in recent decades, demonstrating the long tradition of the artist’s novel and also its centrality in the contemporary imaginary. In spite of this continuous presence, however, in Italy there is a lack of studies specifically dedicated to this character, which requires different methodological tools due to its location at the intersection of different levels of the construction of the text meaning. The key notions elaborated in the field of visual studies – today dominant in the interactions between literature and visual arts – need to be integrated with the investigation of narratological and sociological aspects that his figure calls into question. By contextualizing the problem and analyzing the implications that this character determines within a narration, in this paper we propose a first, embryonic attempt to elaborate the foundations of a theory of the character-artist in the contemporary Italian novel, in order to give a methodological basis for future insights.